State of Financial Literacy among Women in Rural Areas: With Special Reference to Hamirpur District - Dr Ampu Harikrishnan, Sunita Kumari (International Journal of Advanced Science and Technology, 2020)
dia is a country where the percentage of female population is less than the proportion of the malepopulation. According to the child sex ratio published by UNICEF, birth rate of females is decliningsteadily. Child sex ratio in India was 947 girls for 1,000 boys in the year 1991. Rural areas of ourcountry, still the finance related decisions are taken by the male counterparts and women areexcluded from the process tough the government and related agencies had made a lot of efforts tobalance the situation but then again the thought process of the society takes time to evolve. Thispresent study will throw some light on the related issue and try to evaluate the scenario of financialliteracy of women in the rural areas. Hamirpur district of Himachal Pradesh is selected as researcharea, sample size of the study is 200 women from rural area. This is a primary data based study andSPSS 20.0 is used to analyze the data.